Strategi Menjembatani Kesenjangan Generasi Orang Tua-Anak dalam Pewarisan Nilai Kekristenan di Era Digital - Abraham, Martha Luciana; Hermanto, Yanto Paulus (STT Pelita Dunia, 2025)
The generational gap between parents and children in the digital era presents new challenges in the transmission of Christian values. This study was conducted in response to differences in worldview, communication styles, ways of thinking, and levels of digital competence that may weaken the family’s function as the primary context for faith formation. The aim of this research is to formulate strategies to bridge the parent-child generational gap so that the transmission of Christian values remains relevant and effective in the digital age. This study employs a qualitative method through a literature review of reputable academic sources. The findings propose an integrative strategy that includes strengthening relational communication within the family, optimizing and regulating the use of digital media, as well as providing digital literacy training for parents in order to reduce the knowledge and skill gap with their children. Discipleship, parenting training, and pastoral counseling also emerge as essential components that can be implemented complementarily to support the faith formation process within the family. Overall, the study indicates that transmitting Christian values in the digital era requires creative, dialogical, and contextually grounded approaches, while maintaining collaborative partnership between the family and the church. Through such efforts, Christian values can be passed down in a continuous and meaningful manner across generations.